PENGEMBANGAN KAPASITAS (CAPACITY BUILDING) USAHA KECIL DAN MENENGAH BIDANG PERTANIAN DI KECAMATAN RANCABUNGUR KABUPATEN BOGOR - Mu’min Ma’ruf; Ikhbaluddin Ikhbaluddin; Suripto Suripto; Abdurohim Abdurohim (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2021)
Small and Medium Enterprise (Usaha Kecil dan Menengah; UKM) is the backbone of the economy of society, as this sector has accommodated more jobs compared to a large industrial sector. However, the effort of local government in empowering UKM is still not optimal. This issue has become one of the problems for developing the capacity of UKM, particularly the agricultural sector, in Rancabungur District, Bogor Regency. This research aims to describe in-depth the capacity building of this UKM based on the concept developed by UNDP by using a qualitative method with a descriptive approach. Here we highlighted three point of the capacity development: the workforce or human resource (HR), the capital (physical dimension), and the technology. The results show that there are some problems in the capacity building of the UKM’s agricultural sector, notably for its workforce capacity development and the difficulty to access the capital weather for financing or supporting the facilities and infrastructures of the UKM. Moreover, we found that the UKM has a lack of ability for its technology development, notably for its ability to access the information technology and the availability of communication network. Keywords: Capacity Building; Small and Medium Enterprise